2022
DOI: 10.1021/acs.cgd.2c00077
|View full text |Cite
|
Sign up to set email alerts
|

Anticooperativity of Multiple Halogen Bonds and Its Effect on Stoichiometry of Cocrystals of Perfluorinated Iodobenzenes

Abstract: To investigate influences on the topicity of perfluorinated halobenzenes as halogen bond (XB) donors in the solid state, we have conducted a database survey and prepared 18 novel cocrystals of potentially ditopic (13ditfb, 14ditfb) and tritopic (135titfb) XB donors with 15 monotopic pyridines. 135titfb shows high tendency to be mono-or ditopic, but with strong bases it can act as a tritopic XB donor. DFT calculations have shown that binding of a single acceptor molecule on one of the iodine atoms of the XB don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 78 publications
1
33
0
Order By: Relevance
“…Depending on the position of benzoyl substituent, the pyridyl nitrogen atoms are of different basicities and exposed to different steric influences of the neighboring benzoyl group, which can lead to the formation of I···N, and consequently I···O halogen bonds of various geometries and relative strengths. On the other hand, titfb was selected as the halogen-bond donor because it has been shown that with asymmetric ditopic acceptors, it tends to act as a ditopic donor forming halogen-bonded chains …”
Section: Introductionmentioning
confidence: 99%
“…Depending on the position of benzoyl substituent, the pyridyl nitrogen atoms are of different basicities and exposed to different steric influences of the neighboring benzoyl group, which can lead to the formation of I···N, and consequently I···O halogen bonds of various geometries and relative strengths. On the other hand, titfb was selected as the halogen-bond donor because it has been shown that with asymmetric ditopic acceptors, it tends to act as a ditopic donor forming halogen-bonded chains …”
Section: Introductionmentioning
confidence: 99%
“…24,25 The list of studied halogen bond donors and especially halogen bond acceptors grows continuously. Cyclic nitrogen atoms are the most studied and reliable acceptor species, and this is especially the case for pyridine nitrogen atoms, 26 to the point that they are a valuable benchmark for donor evaluation 9,27,28 and studies on acceptor competitiveness. 29,30 In recent years, they have been followed by a variety of other, mostly nitrogen or oxygen atom containing species, such as methoxy, 31−33 nitro, 34−37 hydroxyl, 32,33,38 and nitrile 32,39−41 functional groups, and oxygen atoms in Noxides.…”
mentioning
confidence: 99%
“…15 In this work, four novel Schiff bases (BM, BP, AM, AP; see Scheme 1) were synthesized by a condensation reaction from two diketones, benzoylacetone (B) and acetylacetone (A), and two primary amines, N-( 2 these acceptors; however, because of the geometric disposition of bonded atoms and its basicity (in comparison with the other sites, see above), this atom is not an expected acceptor site. As halogen bond donors, we selected two perfluorinated aromatic halogen bond (XB) donors, 1,4diiodotetrafluorobenzene (14tfib) as a linear ditopic donor and 1,3,5-triiodo-2,4,6-trifluorobenzene (135tfib) as a potentially tritopic donor 28 (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the cocrystal with the linear donor 14tfib , tpyr molecules form 2D networks through C–H···O hydrogen bonding, and these networks are connected by I···S halogen bonding into a 3D network. On the other hand, in the cocrystal with the potentially tritopic 60 and nonlinear donor 135tfib , only halogen bonds are formed with the oxygen and sulfur atoms, leading to the formation of first, a halogen bonded chain, and then a halogen bonded layer when combined with I···I halogen bonds between donor molecules themselves. The only significant intermolecular hydrogen bonds are of C–H···F type, and they connect two adjacent halogen bonded layers.…”
mentioning
confidence: 99%